Predicting Undesired Treatment Outcomes With Machine Learning in Mental Health Care: Multisite Study - Kasper Van Mens; Joran Lokkerbol; Ben Wijnen; Richard Janssen; Robert de Lange; Bea Tiemens (JMIR Medical Informatics, 2023)
Abstract BackgroundPredicting which treatment will work for which patient in mental health care remains a challenge. ObjectiveThe aim of this multisite study was 2-fold: (1) to predict patients’ response to treatment in Dutch basic mental health care using commonly available data from routine care and (2) to compare the performance of these machine learning models across three different mental health care organizations in the Netherlands by using clinically interpretable models. MethodsUsing anonymized data sets from three different mental health care organizations in the Netherlands (n=6452), we applied a least absolute shrinkage and selection operator regression 3 times to predict the treatment outcome. The algorithms were internally validated with cross-validation within each site and externally validated on the data from the other sites. ResultsThe performance of the algorithms, measured by the area under the curve of the internal validations as well as the corresponding external validations, ranged from 0.77 to 0.80. ConclusionsMachine learning models provide a robust and generalizable approach in automated risk signaling technology to identify cases at risk of poor treatment outcomes. The results of this study hold substantial implications for clinical practice by demonstrating that the performance of a model derived from one site is similar when applied to another site (ie, good external validation).